KCNA1 gain‐of‐function epileptic encephalopathy treated with 4‐aminopyridine. Issue 4 (15th February 2023) - Müller, Peter; Takacs, Danielle S.; Hedrich, Ulrike B. S.; Coorg, Rohini; Masters, Laura; Glinton, Kevin E.; Dai, Hongzheng; Cokley, Jon A.; Riviello, James J.; Lerche, Holger; Cooper, Edward C.
Abstract: Precision medicine for Mendelian epilepsy is rapidly developing. We describe an early infant with severely pharmacoresistant multifocal epilepsy. Exome sequencing revealed the de novo variant p.(Leu296Phe) in the gene KCNA1, encoding the voltage‐gated K + channel subunit KV 1.1. So far, loss‐of‐function variants in KCNA1 have been associated with episodic ataxia type 1 or epilepsy. Functional studies of the mutated subunit in oocytes revealed a gain‐of‐function caused by a hyperpolarizing shift of voltage dependence. Leu296Phe channels are sensitive to block by 4‐aminopyridine. Clinical use of 4‐aminopyridine was associated with reduced seizure burden, enabled simplification of co‐medication and prevented rehospitalization.